IMPROVING DRAMA SCRIPT OF WRITING SKILLS WITH USING THE MEDIA FOLK STORY - Bangun Verdana, Rahmayanti, Wulandari (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2024)
The aims of the research was to describe the ability to write drama scripts with folklore media in students. The method used in this research is quantitative descriptive, and the sample in this research was 34 students in class XI B3 of SMA Negeri 2 Kotabaru. The Techniques Data collection used in the observation, interviews, documentation and tests. Based on the results of the research, it can be concluded that the aspect of the suitability of the drama content with a percentage of 61.8% is stated as good, the aspect of the completeness of the intrinsic elements of the drama with a percentage of 44.1% is stated as good, the aspect of the completeness of the structure of the drama script with a percentage of 64.7% is stated as good, the language rules of the drama with a percentage of 67.6% is stated as good, and the spelling and writing aspects with a percentage of 82.4% are stated as good, and the ability to write drama scripts with folklore in students is in the good category with evidence of an average value of 78.1. Keywords: Writing Skills, Drama Scripts, Folklore.